Production, Structural and Morphological Characterization of Feather-Reinforced Epoxy Composites - Aydın, Cihat (Niyazi BULUT, 2023)
The use of bird feathers as filler for epoxy offers an environmentally friendly method for developing composites and coatings. In this study, feather-filled epoxy composite coatings have been developed for use in new generation coatings and production. The structural properties of the produced composites were investigated using XRD, F-TIR and surface morphologies using Scanning Electron Microscopy (SEM). With the help of these analyses, the surface properties of the composites such as wettability and morphology were determined. This green approach to the development of an epoxy/feather coating allows for to replacement of metal parts used in many modern industries or to improve the performance and safety of existing parts
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri